VD_FINDINFO Jug / 2020 / 401 vom 22. Mai 2020 - VD Tribunal cantonal (2020)
FRAIS JUDICIAIRES, PROCÉDURE ÉCRITE, ORDONNANCE PÉNALE, CONDAMNATION | 406 al. 1 let. d CPP (CH), 426 al. 1 CPP (CH), 426 al. 3 CPP (CH)